2014
DOI: 10.4028/www.scientific.net/amr.900.445
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Rockfill Particle Breakage

Abstract: As the high concrete faced rockfill dams construction, grain breakage gradually become the factors that influence the high dam construction which can not be ignored. This text based on the master of rockfill of shuibuya dam as the experimental material, getting and analyzing the particle breakage data under different confining pressure through the large-scale triaxial test, and the results show that the particle breakage index increases with the increase of confining pressures. The relationship between particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Ye [12] carried out a series of shock loading tests with different influencing factors (initial gradation, water content, compaction coefficient),found that regardless of the initial gradation and moisture content, under shock loading, the degree of particle breakage increases with the compaction coefficient. Xu [13] conducted large-scale triaxial tests with Shuibuya rockfill as the test material, and found that the particle breakage index increased with the increase of confining pressure. Sun [14] carried out a consolidated drainage triaxial test with a maximum deformation of 25% for the rockfill material of the high-face concrete rockfill dam Shuibuya Dam, and found that the rockfill material will undergo obvious particle breakage under the action of high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ye [12] carried out a series of shock loading tests with different influencing factors (initial gradation, water content, compaction coefficient),found that regardless of the initial gradation and moisture content, under shock loading, the degree of particle breakage increases with the compaction coefficient. Xu [13] conducted large-scale triaxial tests with Shuibuya rockfill as the test material, and found that the particle breakage index increased with the increase of confining pressure. Sun [14] carried out a consolidated drainage triaxial test with a maximum deformation of 25% for the rockfill material of the high-face concrete rockfill dam Shuibuya Dam, and found that the rockfill material will undergo obvious particle breakage under the action of high pressure.…”
Section: Introductionmentioning
confidence: 99%